Effects of moderate shade and irrigation with eutrophicated water on the nitrogen economy of Mediterranean oak seedlings - Castro-Díez, Pilar; Navarro, Javier; Maestro, Melchor (Flora - Morphology, Distribution, Functional Ecology of Plants, 2008)
We evaluated the effects of moderate shade (43% vs. 100% of full sunlight) and irrigation with eutrophicated river water (daily vs. alternate-day watering) on growth and nitrogen economy of seedlings of three Mediterranean oak species, two evergreen (Quercus coccifera, Quercus ilex subsp. ballota) and a deciduous (Quercus faginea), grown in pots outdoors. Seedling biomass, N pool, N concentration and N losses by litter fall were measured at the beginning (March 2002) and end (November 2002) of a growing season. All species showed an increase of biomass and N pool under shade and/or high irrigation, while only Q. coccifera – from more arid regions – did the same under full sunlight and low irrigation. At the end of the experiment, biomass of the evergreens was higher in shade than in sun, and in high than in low irrigation, while Q. faginea – from more humid zones – responded to irrigation only. Shade-induced growth was accompanied by a decline in N concentration in the evergreens, but irrigation reduced N concentration only of Q. faginea. Shade, but not irrigation, reduced above-ground N loss. We conclude that both treatments differentially affected the evergreen and the deciduous oaks, probably due to differences in plant hydraulic and stomatal conductance. Although both treatments have similar effects on the growth of evergreens, they produced different effects on seedling N economy, which may have important consequences on future ﬁeld seedling performance
Keywords: deciduous tree; Drought stress; evergreen tree; leaf shedding; Quercus; seedling growth

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens